Our sixties : an activist's history - Lauter, Paul (University of Rochester Press, 2020)
Today, some fifty years after, we celebrate - or excoriate - "the Sixties." Using his wide-ranging experience as an activist and writer, Paul Lauter examines the values, the exploits, the victories, the implications, and sometimes the failings, of the "Movement" of that conflicted time. In Our Sixties, Lauter writes about movement activities from the perspective of a full-time participant: 1964 Mississippi freedom schools; Students for a Democratic Society (SDS); the Morgan community school in Washington, DC, which he headed; a variety of antiwar, antidraft actions; the New University Conference, a radical group of faculty and graduate students; The Feminist Press, which he helped found; and the United States Servicemen's Fund, an organization supporting antiwar GIs. He got fired, got busted, got published, and even got tenure. He honed his skills writing for the New York Review of Books among other magazines. As a teacher he created innovative courses ranging from "Revolutionary Literature" and "Contesting the Canon" to "The Sixties in Fiction, Poetry, and Film." He led the development of the groundbreaking Heath Anthology of American Literature and remains its general editor. Lauter's book offers both a retrospective look at the social justice struggles of the Sixties and an account of how his participation in these struggles has shaped his life. Social history as well as personal chronicle, this account is for those who recall that turbulent decade as well as for those who seek to better understand its impact on American politics and society in our current era.